Marcinkiewicz-type strong means of Fourier—Laplace series - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We obtain estimates for Marcinkiewicz-type strong means of the Fourier—Laplace series of continuous functions in terms of the best approximations.